Integrated phenotypic and genotypic approach for characterization of local questing hard tick, Dermacentor compactus (Acari: Ixodidae) - Ernieenor Faraliana Che Lah,; Ai Takano,; Ernna George,; Mariana Ahamad, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Identification of a tick species, Dermacentor compactus (Acari: Ixodidae) from Malaysia is still debatable in many aspects and remains poorly studied, especially on the immature stages. This study was conducted to characterize morphologically and molecularly of the D. compactus ticks collected from a forest reserve near the Forest Research Institute of Malaysia (FRIM). A total of three adults (two females and one male) of questing D. compactus ticks on lower vegetation or shrubs were collected by handpicking. Species identification was conducted based on specific illustrated taxonomic keys, and molecular characteristics of D. compactus was analyzed based on mitochondrial 16S rDNA gene (mt-rrs). A neighbor-joining tree was constructed to clarify the genetic variation of the D. compactus. Clustering analysis using mtrrs gene revealed that the sequences of the D. compactus were formed in a monophyletic clade supported with 100% bootstrap value. Furthermore, a low intraspecific variation (1%) was observed amongst the species of D. compactus. Meanwhile, genetic distance of the D. compactus also supported that the species is genetically distinct from the other Dermacentor species with a high interspecific value (>13%). This study reported the first of 16S sequences of the D. compactus from Malaysia. These present results will contribute to the existing genotypic data of this species from Malaysia, thus merit further investigation as potential vector that related to any tick-borne diseases.